Total synthesis, proof of absolute configuration, and biosynthetic origin of stylopsal, the first isolated sex pheromone of strepsiptera - Lagoutte, Roman; Šebesta, Petr; Jiroš, Pavel; Kalinová, Blanka; Jirošová, Anna; Straka, Jakub; Černá, Kateřina; Šobotník, Jan; Cvačka, Josef; Jahn, Ullrich (Chemistry (Weinheim an der Bergstrasse, Germany), 2013)
The asymmetric total synthesis of the diastereomers of stylopsal establishes the absolute configuration of the first reported sex pheromone of the twisted-wing parasite Stylops muelleri as (3R,5R,9R)-trimethyldodecanal. The key steps for the diastereo- and enantiodivergent introduction of the methyl groups are two different types of asymmetric conjugate addition reactions of organocopper reagents to α,β-unsaturated esters, whereas the dodecanal skeleton is assembled by Wittig reactions. The structure of the natural product was confirmed by chiral gas chromatography (GC) techniques, GC/MS and GC/electroantennography (EAD) as well as field tests. An investigation into the biosynthesis of the pheromone revealed that it is likely to be produced by decarboxylation of a 4,6,10-trimethyltridecanoic acid derivative, which was found in substantial amounts in the fat body of the female, but not in the host bee Andrena vaga. This triple-branched fatty acid precursor thus seems to be biosynthesized de novo through a polyketide pathway with two consecutive propionate-propionate-acetate assemblies to form the complete skeleton. The simplified, motionless and fully host-dependent female exploits a remarkable strategy to maximize its reproductive success by employing a relatively complex and potent sex pheromone.
Keywords: Animals; Female; ženské pohlaví; sexuální lákadla; chování zvířat; Esterification; esterifikace; Stereoisomerism; stereoizomerie; Aldehydes; aldehydy; Male; plynová chromatografie s hmotnostně spektrometrickou detekcí; nitrily; Bees; Nitriles; Behavior, Animal; Gas Chromatography-Mass Spectrometry; včely; zvířata; mužské pohlaví; Sex Attractants